1987
DOI: 10.1037/0022-006x.55.6.860
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral and pharmacologic interventions for childrens' distress during painful medical procedures.

Abstract: This study evaluated the efficacy of a cognitive-behavioral intervention package and a low-risk pharmacologic intervention (oral Valium), as compared with a minimal treatment-attention control condition, in reducing children's distress during bone marrow aspirations. The subjects were 56 leukemia patients who ranged in age from 3 years to 13 years. The three intervention conditions were delivered in a randomized sequence within a repeated-measures counterbalanced design. Dependent outcome measures included obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(109 citation statements)
references
References 22 publications
4
103
0
1
Order By: Relevance
“…8 Guided imagery, when used in isolation, has not proved effective for this younger population, 42,77 perhaps because it is difficult to sustain for long periods of time. Other studies have also found that distress-reduction effects did not persist when the therapist (coach) was not present, 73,74 making this strategy less feasible if adequate personnel are not available.…”
Section: Cognitive Behavioral Interventions Before Cardiac Catheterizmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Guided imagery, when used in isolation, has not proved effective for this younger population, 42,77 perhaps because it is difficult to sustain for long periods of time. Other studies have also found that distress-reduction effects did not persist when the therapist (coach) was not present, 73,74 making this strategy less feasible if adequate personnel are not available.…”
Section: Cognitive Behavioral Interventions Before Cardiac Catheterizmentioning
confidence: 99%
“…Numerous studies document increased efficacy when preprocedure preparation includes training in cognitive-behavioral interventions, 7,49,72 particularly for children and adolescents with previous medical experience. 45,73,74 The therapeutic effects achieved by use of cognitive behavioral interventions have been attributed to a variety of cognitive and physiological responses, including decreased pain secondary to muscle relaxation, habituation of body sensations, distraction, altered perception of the event, increased positive reinforcement from self and others, and enhanced sense of mastery or internal locus of control. Interventions include guided imagery, positive selfinstruction, progressive muscle relaxation and conscious breathing.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 99%
“…For example, Powers 52 found that behavioral interventions for pediatric acute painful procedures met criteria for "empirically supported" treatments. The intervention packages typically included relaxation, 53 breathing exercises, 54 rehearsal, 55 reinforcement for appropriate behavior, 53 and imagery. 56 A key component across these interventions, especially for young children, is distraction.…”
Section: Intervention During Venous Accessmentioning
confidence: 99%
“…The second study 57 was a comparison of the CBT package with oral diazepam and an attention-control condition (30 minutes of cartoon watching prior to the BMA), delivered in the context of a repeated measures, counterbalanced design. A total of 56 children with leukaemia, aged 3-13 years, were studied.…”
Section: Cognitive-behavioural Intervention Human Beings Are Active Pmentioning
confidence: 99%
“…Jay et al 56,57 developed a multicomponent intervention 'package' of cognitive-behavioural techniques (CBT) designed to teach effective coping skills and to reduce children's distress during BMA and LP. This consists of five primary components: filmed modelling, incentive, breathing exercises, emotive imagery and distraction, and behavioural rehearsal.…”
Section: Cognitive-behavioural Intervention Human Beings Are Active Pmentioning
confidence: 99%